Voltammetric Detection of Cu²⁺ Using a Napa Soil-Derived NiAl₂O₄/MWCNT-Modified Glassy Carbon Electrode - Sani, Ihya Zakira; Mawardi, Mawardi; Kurniawati, Desy; Khair, Miftahul; Suryani, Okta (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Copper ions (Cu²⁺) are essential trace elements but may become toxic at elevated concentrations, requiring reliable monitoring methods. In this study, a NiAl₂O₄/MWCNT-modified glassy carbon electrode (GCE) derived from napa soil was developed for the voltammetric determination of Cu²⁺ ions. The modified electrode was prepared by combining NiAl₂O₄ synthesized from napa soil with multi-walled carbon nanotubes (MWCNTs) through a drop-casting technique. Electrochemical characterization demonstrated that the incorporation of NiAl₂O₄ and MWCNTs significantly enhanced the electrochemical performance of the electrode by improving electron-transfer efficiency and increasing the electroactive surface area. The modified electrode exhibited a strong voltammetric response toward Cu²⁺ ions, while HClO₄ was identified as the most suitable supporting electrolyte among the investigated media. Selectivity studies showed that Cu²⁺ remained detectable in the presence of Pb²⁺, although partial signal suppression was observed at higher Pb²⁺ concentrations. These findings indicate that the NiAl₂O₄/MWCNT-modified GCE is a promising low-cost and sustainable platform for Cu²⁺ determination in aqueous environments.